2022
DOI: 10.1002/ecs2.3996
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and genetic diversity elucidate rarity and vulnerability of an endangered riparian plant

Abstract: Environmental change, accelerated by anthropogenic activities, threatens many species and can be especially challenging for rare species given their potentially limited capacity for migration and adaptation relative to more common species. The ability to acclimate via phenotypic plasticity could provide an important path to species persistence in the face of such change. We investigated the responses of an endangered plant species endemic to a highly dynamic riparian habitat in southeastern Tennessee, USA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 93 publications
(108 reference statements)
1
14
0
Order By: Relevance
“…Plant species can differ extensively in their plastic responses to environmental change (Sultan, 2000; Nicotra & Davidson, 2010; Godoy et al ., 2012; Dangremond et al ., 2015), and widespread species could have relatively high plasticity owing to greater spatial variation across their ranges (Murray et al ., 2002). Few studies explicitly contrasted plasticity across rare and common congeners (Liao et al ., 2006; Lovell & McKay, 2015; Hirst et al ., 2017; Rutherford et al ., 2017; Boyd et al ., 2022), even though numerous studies exposed rare and common species to multiple environmental conditions. Additionally, the plasticity studies in our dataset mostly neglected to test whether plasticity confers a fitness advantage in rare or common species (but see Boyd et al ., 2022), which is critical because plasticity can be a passive or maladaptive stress response (Palacio‐López et al ., 2015; Hendry, 2016; Bonser, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plant species can differ extensively in their plastic responses to environmental change (Sultan, 2000; Nicotra & Davidson, 2010; Godoy et al ., 2012; Dangremond et al ., 2015), and widespread species could have relatively high plasticity owing to greater spatial variation across their ranges (Murray et al ., 2002). Few studies explicitly contrasted plasticity across rare and common congeners (Liao et al ., 2006; Lovell & McKay, 2015; Hirst et al ., 2017; Rutherford et al ., 2017; Boyd et al ., 2022), even though numerous studies exposed rare and common species to multiple environmental conditions. Additionally, the plasticity studies in our dataset mostly neglected to test whether plasticity confers a fitness advantage in rare or common species (but see Boyd et al ., 2022), which is critical because plasticity can be a passive or maladaptive stress response (Palacio‐López et al ., 2015; Hendry, 2016; Bonser, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies explicitly contrasted plasticity across rare and common congeners (Liao et al ., 2006; Lovell & McKay, 2015; Hirst et al ., 2017; Rutherford et al ., 2017; Boyd et al ., 2022), even though numerous studies exposed rare and common species to multiple environmental conditions. Additionally, the plasticity studies in our dataset mostly neglected to test whether plasticity confers a fitness advantage in rare or common species (but see Boyd et al ., 2022), which is critical because plasticity can be a passive or maladaptive stress response (Palacio‐López et al ., 2015; Hendry, 2016; Bonser, 2021). Studies that compare plasticity in rare and common species and link plasticity to performance in the context of probable environmental change could test the hypothesis that geographically restricted species or habitat specialists could be limited in their ability to acclimate to a broader range of environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We included population as a random effect in these models. A significant interaction indicated that B. perstellata and B. laevigata responded differently to a change in the environmental factor (i.e., that the two species exhibited differences in plasticity; see Boyd, Odell, et al, 2022). To account for the numerous traits analyzed to assess plasticity, we used corrected p‐ values to minimize the false discovery rate (FDR; Benjamini & Hochberg, 1995).…”
Section: Methodsmentioning
confidence: 99%